2014
DOI: 10.1002/ejlt.201400393
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of Albizia lebbeck and Albizia saman seed oils: Presence of coronaric acid

Abstract: In this work, the fatty acid profiles of the seed oils of Albizia lebbeck and Albizia saman (Samanea saman) are reported. The oils were analyzed by GC, GC-MS and NMR. The most prominent fatty acid in both oils is linoleic acid (30-40%), followed by palmitic acid and oleic acid for A. lebbeck and oleic acid and behenic acid for A. saman. Both oils contain slightly more than 30% saturated fatty acids with stearic, eicosanoic and tetracosanoic acids present as well as odd-numbered saturated fatty acids in minor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…No less common or unusual fatty acids such as cyclic, epoxy or hydroxy fatty acids were observed. The absence of such less common fatty acids appears to be typical for most oils from plants of the Fabaceae family but in the seed oils of species of the Albizia and Acacia, which also belong to the Fabaceae family but different genera, fatty acids with cyclic moieties were observed [36]. The fatty acid profile observed in the present work largely agrees with the fatty acid profiles reported previously [27,28] which also indicate similar amounts of saturated fatty acids ( Table 1).…”
Section: Resultssupporting
confidence: 90%
“…No less common or unusual fatty acids such as cyclic, epoxy or hydroxy fatty acids were observed. The absence of such less common fatty acids appears to be typical for most oils from plants of the Fabaceae family but in the seed oils of species of the Albizia and Acacia, which also belong to the Fabaceae family but different genera, fatty acids with cyclic moieties were observed [36]. The fatty acid profile observed in the present work largely agrees with the fatty acid profiles reported previously [27,28] which also indicate similar amounts of saturated fatty acids ( Table 1).…”
Section: Resultssupporting
confidence: 90%
“…Literature reports also show that behenic and lignoceric acids were present in the seed oils of the Albizia genus which also belongs to the Fabaceae family. A recent report on the fatty acid composition of Albizia lebbeck and Albizia saman revealed that the seed oil of Albizia saman was found to contain 13.6 and 2.3% of behenic and lignoceric acid, respectively; whereas Albizia lebbeck showed lower contents of these fatty acids (Knothe et al, 2015). The presence of very long chain fatty acids in seed oils in higher amounts is advantageous as it provides an opportunity to employ these oils in low calorie fat applications (Haumann, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The coronaric acid content of Albizia resembles that of Acacia species with both genera belonging to the Fabaceae family. The mass spectrum of the pyridylcarbinol (picolinyl) ester of coronaric acid is reported (Knothe et al, 2014). Current literatures markedly lacked data and information about synthesis of alkyd resin from Albizia lebbeck seed oil.…”
Section: Introductionmentioning
confidence: 99%